Urban consumption spaces and practices of women in low-income urban settlements : a case study in Khlong Toey, Bangkok : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Finlayson, Jennifer (Massey University, 2015)
Consumption related research focuses strongly on the experiences of the Anglo-American middle classes, and less is known about what consumption spaces and practices represent to those living in developing countries. Low-income urban women in developing countries seem particularly invisible, and more especially so rural-urban migrant women. Using a qualitative approach, this thesis explored the role and significance of urban consumption spaces and practices in the everyday lives of low-income women living in Khlong Toey, Bangkok. Findings show that consumption practices represent more than provisioning, they are a way that women meet the families’ basic needs and demonstrate their care and strong connections for both their rural and urban families. Consumption practices contribute to the role that women have in making consumption related household decisions and active engagement in consumption promotes improving autonomy. The adoption of urban consumption practices affects both the women’s sense of belonging and their perception of fitting in to their urban environment. Furthermore, the adoption of urban ways by the women, including new ideals, behaviours and material goods are also exported back to their rural villages, subsequently improving women’s families’ social status and blurring traditional lines of social delineation that exist between rural and urban society. Consumption practices enable women to invest in their families’ futures. This thesis demonstrates that it is not only through women’s production that development outcomes are enabled, but through consumption as well. This is significant, as framed within development discourses, consumption contributes to women gaining autonomy within gender development; and consumption practices demonstrate provisioning and maintaining familial commitment within urban and rural livelihoods.
Keywords: Consumption (Economics); Poor women; Low-income women; Rural-urban migration; Bangkok; Thailand